P256 Bowel contrast-enhanced ultrasound perfusion imaging in the evaluation of Crohn's disease patients. (25th January 2019) - Laterza, L; Ainora, M E; Garcovich, M; Poscia, A; Lupascu, A; Riccardi, L; Scaldaferri, F; Armuzzi, A; Gasbarrini, A; Rapaccini, G L; Pompili, M; Zocco, M A
Abstract: Background: Evaluation of inflammation in Crohn's disease (CD) is crucial for treatment planning and monitoring. The use of contrast enhanced ultrasound (CEUS) could be important in the diagnosis and follow-up since it is a non-invasive and easily repeatable method. We aimed to prospectively evaluate the role of CEUS in CD. Methods: In total, 54 patients with active ileal CD starting infliximab were enrolled. Clinical assessment, laboratory tests and CEUS were performed at baseline (T0) and after 2 (T1), 6 (T2) and 12 weeks (T3) of treatment to assess variations in peak intensity (PI), area under the curve (AUC), slope of wash in (Pw), time to peak (TP), mean transit time (MTT). Deep remission was defined as SES-CD = 0 or decreased of at least 1 unit plus CDAI < 70 at T3. Clinical relapse was assessed up to 3 months. Results: 70% of patients achieved deep remission (responders). The delta between T0 and T1 was significantly different in responders and non-responders in PI, AUC, Pw, and MTT. Ninety-five per cent of patients showed a reduction in PI, 100% in AUC, 84% in Pw, 26% in TP and 50% in MTT. There was a good correlation between ratio in CEUS parameters between T1-T0 and T2-T0 and T3-T0. The eight patients who relapsed showed lower mean percentage reduction in delta PI between T1 and T0 and between T2 and T0 compared with patients in remission (−8.4 vs. −20.76, p = 0.038) and a new increase at T3 (15.6 vs. −62.9, p < 0.001). No significant differences in delta AUC have been found in relapsers and non relapsers at T1 (−25 vs. −23.7, p = ns), but reduction in AUC values are lower at T2 (−53 vs. −32.1, p = 0.007) and T3 (−62.4 vs. −3.9, p < 0.001) in relapsers. About Pw, at T1 and T2 mean percentage of reduction are higher in patients who will maintain remission (−23.2 vs. −1.9, p = 0.008 and −38.6 vs. −15.8, p = 0.006, respectively) with a return to results similar to baseline at T3 in relapsers (−51 vs. −0.42, p < 0.001). Conclusions: CEUS could be useful as reliable predictor of deep remission and clinical relapse in patients with CD treated with infliximab.